Assessment of Thickness of Macular Edema on Optical Coherence Tomography in Diabetic Patients Treated with Anti-Vascular Endothelial Growth Factor: Macular Edema on Optical Coherence Tomography with Anti-VEGF Factor - Soomro, Inam Majid; Ali, Imran; Khoso, Ayaz Ali; Kandhro, Prince Aakash Gul; Gopang, Zakaullah; Abbasi, Safdar Ali (Pakistan Journal of Health Sciences, 2025)
Diabetes is becoming more commonplace worldwide with potential causes. Diabetic retinopathy is a serious ocular complication that affects working-age adults and causes moderate to severe vision loss. Objective: To determine the outcome of anti-VEGF by optical coherence tomography (OCT) in DME thickness. Methods: A prospective (interventional) study was carried out at the Chandka Medical College Hospital's Department of Ophthalmology at SMBB Medical University, Larkana. The study included all individuals over the age of 15 who had diabetes mellitus of any kind. SPSS version 26 was used for data analysis. Result: Patients were 64.8 ± 14.2 years old on average, had a BMI of 33.56 ± 7.85 kg/m2, and had been on DME for an average of 8.06 ± 4.23 years. There were 17 (34%) female patients and 33 (66%) male patients out of 50. The most common risk factor among 50 patients was hyperlipidemia, 45(90%) followed by hypertension 43 (86%), anemia 42 (84%), insulin dependent, 37 (74%), obesity31(62%), chronic renal failure, 28 (56%) and smoking, 26 (52%). Conclusion: OCT can be used to accurately measure retinal thickness brought on by DME. OCT can therefore be a helpful technique in predicting the functional outcome and assessing how well anti-VEGF medication works for individuals with DME. Anti-VEGF therapy results in rapid and sustained thickness reduction on OCT, generally correlating with improvements in visual acuity. The outcome of anti-VEGF therapy in diabetic macular edema (DME), as measured by OCT, typically shows a significant reduction in central retinal thickness (CRT) or central subfield thickness (CST).